Ethics in the workplace - Bredeson, Dean; Goree, Keith (South-Western/Cengage Learning, 2012)
Combines foundation in classic and contemporary theory, examples and analysis drawn from the workplace, ethical decision-making models, and a constant focus on self-reflection and moral reasoning